Gene-gene and gene-environment interactions in lipodystrophy: Lessons learned from natural PPARγ mutants - Broekema, M.F.; Savage, D.B.; Monajemi, H.; Kalkhoven, E. (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2019)
Monogenic lipodystrophies are a heterogeneous group of rare disorders characterized by a lack of adipose tissue (AT), all of which predispose patients to the development of insulin resistance and its related metabolic sequelae. The extent of AT loss ranges from partial, as in familial partial lipodystrophy (FPLD), to a total absence of metabolically active AT in congenital generalized lipodystrophy (CGL) and is generally associated with the severity of metabolic complications. Significant genetic, allelic, phenotypic, and clinical heterogeneity exists among the lipodystrophies. Patients with FPLD3 due to mutations in the PPARG gene, which encodes a key transcriptional regulator of adipocyte development and function, provide a particularly striking example of this heterogeneity. We will present several gene-gene and gene-environment factors and mechanisms that are critical for adequate PPARγ expression and activity in AT and discuss how these interactions potentially contribute to the observed spectrum of FPLD3 phenotypes. Comparable mechanisms may play a role in other types of lipodystrophies too, and their elucidation may further improve our molecular understanding of AT dysfunction. •Most genetic lipodystrophies are caused by mutations in single genes.•Significant heterogeneity exists among genetic lipodystrophies.•FPLD3, due to PPARG mutations, provides a striking example of the heterogeneity.•Genetic and environmental factors modulate PPARγ; contributing to FPLD3 variability.•Comparable mechanisms likely have a role in other types of lipodystrophies too.